A leitura na perspectiva de Bakhtin e suas possibilidades na formação do leitor: na educação infantil e no primeiro ano do ensino fundamental - Pileggi, Vanessa Helena [UNESP] (2013)
Overall, in Brazilian schools, the concept of reading does not take into account its possibilities and its meaning for life. But read is assigning meaning to something , make sense, interact with the text read. Thus, the present study addresses the mechanical reading, that without contextualization, performed on a technique by joining letters and syllables loose and also reading social use, consisting of statements, dialogism , polyphony and heteroglossy. It is known that the mechanical reading brings undesirable consequences, including learning problems, such as lack of attention, concentration, memory, imagination. When the reading is taught in a systematic way, with only the goal of the code decoding of written language, destroys social perspectives and intellectual development. It is common, when you offer the children a book, there the difficult disinterest of textual interpretation, because there is no attribute meaning to the content, and even the ability to interact with the text. With the interest in studying the dialogic reading this and the statements and genres, the present study was based on several authors: Bakhtin (1988, 2000), Schneuwly and Dolz (2000), Faraco (2009) and Ponzio (2009) Jolibert (1994), Bajard (2002; 2007) Foucambert (1997) Martins ( 1985) and Smith ( 1999). Aim for this study the following research question: what are the contributions of Mikhail Bakhtin's theory to the teaching of reading from kindergarten through the first grade of elementary school? Our hypothesis is that if they are guaranteed to pre -school and elementary school beginners diversified materials and new approaches in teaching reading and encouragement to her, will be developed in children a taste for the act of reading, so that they can assign meaning and significance, making reading part of their lives...